Genome and Transcriptome Analyses Provide Insight Into the Omega-3 Long-Chain Polyunsaturated Fatty Acids Biosynthesis of Schizochytrium limacinum SR21 - Liang, Limin; Zheng, Xuehai; Fan, Wenfang; Chen, Duo; Huang, Zhen; Peng, Jiangtao; Zhu, Jinmao; Tang, Weiqi; Chen, Youqiang; Xue, Ting (Frontiers in Microbiology, 2020)
Schizochytrium sp. is the best natural resource for omega-3 long-chain polyunsaturated fatty acids. We report a high-quality genome sequence of Schizochytrium limacinum SR21, which has a 63 Mb genome size, with a contig N50 of 2.67 Mb and 6,838 protein-coding genes. Phylogenomic and comparative genomic analyses revealed that DHA-producing Schizochytrium and Aurantiochytrium strains were highly similar and possessed similar genes. Analysis of the fatty acid synthase (FAS) for LC-PUFAs production results in the annotation of all genes in map00062 and map01212. A gene cluster and 10 ORFs related to PKS pathway were found in the genome. 1,402 differentially expressed genes (DEGs) of the treated groups (0.5 g/L yeast extract) were identified by comparing with the control groups (1.0 g/L yeast extract) at 36 h. A weighted gene coexpression network analysis revealed that 2 of 7 modules correlated highly with the fatty acid and DHA contents. The DEGs and transcription factors were significantly correlated with fatty acid biosynthesis, including MYB, Zinc Finger and ACOX. The results showed that these hub genes are regulated by genes involved in fatty acid biosynthesis pathways. The results providing an important reference for further research on promoting fatty acid and DHA accumulation in S. limacinum SR21.